Electrophoretic patterns of gliadin as markers of genotypes in the analysis of the durum wheat landrace Kubanka - T. I. Peneva; O. A. Lyapunova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. The collection of durum wheat landraces (Triticum durum Desf.) at VIR contains unique material of the “Russian northern branch”, which is not found in any other collections worldwide. Studying the genetic diversity of such wheat accessions according to their gliadin bands as markers of genotypes is important for identification and conservation of their gene pool authenticity.Materials and methods. For the first time, molecular markers were used to differentiate among 38 accessions of the local durum wheat variety known under the name of “Kubanka”, collected and placed into the VIR collection in the 1910–1940s, and five accessions from the seed genebanks of the USA and Canada. Electrophoretic patterns of gliadin were used as markers of genotypes within the polymorphic cultivar. Recording bands in the form of “protein formulas” allows the researcher to evaluate the polymorphism of each accession and the diversity within the collection. Gliadin analysis was performed on single grains according to the standard method adopted at VIR and approved by ISTA.Results and conclusions. Fourteen major biotypes marked with gliadin bands were identified. Depending on the component composition of the α-zone encoded by alleles of the GLI-2A locus, biotypes were combined into 4 groups. Within the groups, biotypes are determined by alleles of the GLI-1A, GLI-1B, GLI2B loci. Genetically close monotypic accessions and polytypic ones incorporating 2 to 6 biotypes were identified. Group I is typical for the European part of Russia as well as for Kazakhstan and Kyrgyzstan. Accessions of this group can be attributed to the Volga steppe ecotype. Group II biotypes are widespread in Altai Territory, Orenburg and Astrakhan Provinces of Russia; Group III in Stavropol Territory, Russia, and Kyrgyzstan; Group IV only in Altai Territory. The greatest genetic diversity was exhibited by the ‘Kubanka’ accessions from Altai and Krasnodar Territories, and Kyrgyzstan.